Measurements of L-shell X-ray production cross-sections of Ag and Sb by low-energy electron impact. (May 2016) - Zhao, J.L.; An, Z.; Zhu, J.J.; Tan, W.J.; Liu, M.T.
Abstract: The total L-shell X-ray production cross-sections of Ag and Sb elements were measured by detecting the characteristic X-rays induced by the electron impact in the energy range of 6–28 keV. In this experiment, the thin films with thick aluminum substrates were used as the targets, and the experimental setup was improved. The influence of multiple scattering of electrons penetrating the targets films, electrons reflected from the thick aluminum substrates and bremsstrahlung photons produced when incident electrons impacted the targets were corrected by using the Monte Carlo method. The experimental results determined in this paper were compared with some theoretical models and other available experimental data in the literature. It was shown that the L-shell X-ray production cross-sections of Ag and Sb elements measured in this paper were in good agreement with the theoretical predictions within the uncertainties. Highlights: We measured L shell X-ray production cross-sections of Ag and Sb by keV electrons. Corrections for effects of target substrates are made by MC simulations. L shell production cross-sections measured are in good agreement with theories.